Financing the future of elderly care: understanding public acceptance of social insurance for long-term care - Mohamad, Nurul Afidah; Tan, Chi Hau; Seow, Ai Na; Looi, Sing Yan; Mohd Yusoff, Syarah Syahira; Awang, Halimah (Innovative Research Publishing, 2025)
With traditional family-based old-age care declining due to shrinking family structures, formal financial protection for the aging population is increasingly crucial. This is especially given the high cost of long-term care. Acknowledging the limitations of private insurance and tax-based systems, this study explores the potential of social insurance in Malaysia by examining factors influencing its public acceptance. Data collected from a total of 450 respondents were analyzed using SPSS for descriptive statistics and SmartPLS for hypothesis testing. The findings revealed that knowledge-based factors such as financial literacy and financial awareness do not exhibit a significant influence on financial attitude. In contrast, psychological factors such as precautionary motives and trust demonstrate a significant and positive influence on financial attitude. Furthermore, attitude emerges as a significant mediating variable that bridges the relationship between precautionary motives and acceptance, as well as between trust and acceptance. In a nutshell, this study contributes to the existing literature on long-term care financing from the lens of consumer behavior and offers valuable insights for policymaking in navigating the nation’s aging population.